2022
DOI: 10.1097/aci.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Emerging approaches in the diagnosis and therapy in shellfish allergy

Abstract: Purpose of reviewDespite the high prevalence of shellfish allergy, the clinical management of seafood allergy has remained unchanged over decades. Here, we examined the current status in the diagnosis and clinical management of shellfish allergy and highlighted the imminent need for more specific diagnostic methods, as well as effective and safe therapeutic approaches for shellfish allergy.Recent findingsWith the advancement in the molecular identifications and definition of reactive epitopes of shellfish alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Despite the ongoing advancements of different diagnostic techniques, achieving a diagnosis with a single-step test is not easy. Hence, a stepwise approach to conclude the shellfish allergy diagnosis is advised ( Figure 2 ) [ 108 , 109 ].…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the ongoing advancements of different diagnostic techniques, achieving a diagnosis with a single-step test is not easy. Hence, a stepwise approach to conclude the shellfish allergy diagnosis is advised ( Figure 2 ) [ 108 , 109 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Tests can be performed by applying commercial whole allergen extracts, or, by fresh allergens (prick-to-prick tests (PTP)). However, some factors must be taken into consideration when analyzing the results, such as the likelihood of cross-reactivity among shellfish, house dust mites, and cockroaches, the variability of test protocols used, the lack of standardization in allergen preparations used in the test, and the fact that the shelf-life and the stability of the reagent can interfere with the sensitivity and specificity of these conventional tests [ 109 ]. In a study including children and adults, five commercial shellfish SPT extracts reported a high variability of IgE reactivity in immunoblotting [ 112 ], with a sensitivity range of 59–79%.…”
Section: Diagnosismentioning
confidence: 99%
“…The test is based on the idea that the measurement of luciferase’s signal reflects the degree of IgE crosslinking [ 129 ]. ExiLe technology has been promisingly demonstrated to have better diagnostic accuracy than SPTs and sIgE [ 125 , 130 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Since tropomyosin is highly allergenic, research in shellfish immunotherapy has also focused on the development of hypoallergenic variants of tropomyosin to improve the safety of AIT. Hypoallergenic tropomyosin is obtained through methods including enzymatic crosslinking, polypeptide fragmentation and epitope manipulation [ 130 , 148 , 149 ].…”
Section: Managementmentioning
confidence: 99%
“…Specific immunotherapy for foods such as wheat [2], peanuts [3], tree nuts [4], shellfish [5] or milk [6] are able to increase the respective thresholds of reactivity, but they are not able to restore a full persistent tolerance. The use of biologics proved to be safer and more effective [7][8][9], but equally unable to modify the natural history of the disease.…”
mentioning
confidence: 99%